Income management can help you to manage your money better... - Australia. Centrelink ([A.C.T.] : Centrelink, 2010)
Poster advertising Centrelink's "Income management" program which aims to assist people to manage their money to meet essential household needs and expenses. The title appears in black , yellow and white text against a green square background. The words "Food. Rent. Bills. Clothes. Medical. Petrol. Transport" appear overlaid on the right hand side of the green square. "For more information about: how Voluntary Income Management works, how payments are managed, who is eligible, and how to apply for Voluntary Income Management, Phone us on 13 2594" appears below. The Australian Government and Centrelink logos appear in the bottom right corner. "C0671.0911" appears at the foot of the poster in the right corner.
Caption title.
National Library of Australia's copy previously folded, shows horizontal and vertical fold marks.
Keywords: Australia. -- Centrelink -- Posters; Posters, Australian; Australia -- Posters; Australian